2011
DOI: 10.1016/s0924-9338(11)72373-2
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus severity and the relation to depressive symptoms: A critical study

Abstract: IntroductionResearch indicates that subjective tinnitus severity varies among tinnitus patients. One of the variables held responsible for these differences is depression. However the relationship between depression and tinnitus severity was never investigated more in depth.ObjectivesIf depression is responsible for differences in subjective tinnitus severity two conditions need to be fulfilled. First, there should be evidence for the presence of moderate to severe depressive symptomatology in a substantial gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 23 publications
2
26
0
4
Order By: Relevance
“…A recent study also found that tinnitus handicap is more related to somatic symptoms of DEP, as compared to affective or cognitive symptoms [33]. The higher sensitivity of the TQ to SOM can be explained by the fact that four items of the TQ address specifically somatic symptoms.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A recent study also found that tinnitus handicap is more related to somatic symptoms of DEP, as compared to affective or cognitive symptoms [33]. The higher sensitivity of the TQ to SOM can be explained by the fact that four items of the TQ address specifically somatic symptoms.…”
Section: Discussionmentioning
confidence: 94%
“…Greater lifetime prevalence of major DEP in a group of tinnitus patients compared to controls has also been demonstrated [9,16]. However, it has to be considered that the significant correlation between self-report instruments that assess tinnitus severity and DEP is partly explained by content overlap of some items in these questionnaires [33,12].…”
Section: Discussionmentioning
confidence: 99%
“…Three factors were identified to have a unique significant effect on tinnitus severity when measured on both the TQ and THI: (1) percentage of tinnitus awareness during the day, (2) self-reported depression and/or anxiety, and (3) tinnitus loudness. A close relationship between tinnitus and depression and/or anxiety has been demonstrated multiple times [9][10][11][12][13][14]. Other studies did not show a positive correlation between anxiety or depression and tinnitus [10,15].…”
Section: Discussionmentioning
confidence: 96%
“…Eleven of these studies evaluated only a small number of potential variables and were thus not able to perform a contributory multivariate analysis (Axelsson & Ringdahl 1989;Halford & Anderson 1991;Henry & Wilson 1995;Meric et al 1998;Andersson et al 2001;Mazurek et al 2010;Pinto et al 2010;Mondelli & da Rocha 2011;Schlee et al 2011;Ooms et al 2011;Ooms et al 2012). Multivariate analyses are essential in finding uniquely related variables because these take into account the interdependencies between different variables.…”
Section: Introductionmentioning
confidence: 99%